Supra-(carbon nanodots) with a strong visible to near-infrared absorption band and efficient photothermal conversion - Li, Di; Han, Dong; Qu, Song-Nan; Liu, Lei; Jing, Peng-Tao; Zhou, Ding; Ji, Wen-Yu; Wang, Xiao-Yun; Zhang, Tong-Fei; Shen, De-Zhen (Light, science & applications, 2016)
A novel concept and approach to engineering carbon nanodots (CNDs) were explored to overcome the limited light absorption of CNDs in low-energy spectral regions. In this work, we constructed a novel type of supra-CND by the assembly of surface charge-confined CNDs through possible electrostatic interactions and hydrogen bonding. The resulting supra-CNDs are the first to feature a strong, well-defined absorption band in the visible to near-infrared (NIR) range and to exhibit effective NIR photothermal conversion performance with high photothermal conversion efficiency in excess of 50%. Nanoparticles: working together for longer wavelengths Carbon nanostructures with superb optical properties in both the visible and near-infrared regions have been synthesized by a team in China. Carbon nanodots (CNDs) are a kind of biocompatible nanomaterials, making them ideal for biological applications. Their absorption wavelengths can be controlled, but this has so far been limited to ultraviolet, blue and green regions. Now, Songnan Qu and co-workers from the Changchun Institute of Optics, Fine Mechanics and Physics and Jilin University show that assembling CNDs creates nano-sized aggregates that absorb across the visible range and into the near-infrared. They created the CNDs by hydrothermal treatment of a solution and freeze-drying. The H 2 O molecules cause CNDs to stick together due to possible electrostatic interactions and hydrogen bonding. The extended optical properties of these so-called supra-CNDs could prove useful in photothermal conversion for nanomedicine.